(untitled) (Texas Journal of Medical Science, 2022)
Leiomyosarcoma (LMS) is a rare malignant tumor of smooth muscle origin that usually arises from soft tissues, reduced due to smooth muscle or vessel walls of venous origin. Renal leiomyosarcomas arise from the smooth muscle tissues of the renal pelvis, renal capsule, or renal vessels, and are most commonly encountered. This article presents clinical cases of diagnosis and surgical treatment of renal leiomyosarcoma found in the renal pelvis, complicated by extended thrombosis of the vena cava inferior (VCI).